Barriers to timely treatment of undescended testis in Pakistani patients - Ali, Nawazish; Furqan Ullah Khan; Mohammad Osama (Journal of the Pakistan Medical Association, 2025)
The reason for writing this letter is that recently during our surgical unit rotation we received a 30-year-old patient with infertility and bilateral Undescended testis (UDT), for which surgical procedure was done; upon relevant literature review there was little work done regarding this common problem: ‘Why patients of undescended testis present beyond the optimal age for treatment’.1 Cryptorchidism is defined as a failure of one or both testes to descend toward the scrotum. It is the most frequent congenital anomaly among boys. The incidence of cryptorchidism in full-term infants is 1-4%, while in preterm up to 45%. In newborns spontaneous descent of testis up to 3 month of age occurs which further decreases overall incidence rate. Routine thorough Physical examination is required after birth for early diagnosis of the UDT. Orchidopexy is recommended before 2nd birthday of child, Recent suggestion for orchidopexy age is 6-12 months.2 Delayed diagnosis and treatment can cause testicular atrophy, malignant changes, torsion, subfertility and psychological effects. Late presentation has been reported as indicator of poor health system and lack of awareness. Success rate of surgery without further complication is high in early diagnosis and treatment for UDT.3 In Pakistan, Patients with undescended testis often present beyond the optimal age for treatment due to several factors. The reasons might be due to Lack of Awareness, Cultural Beliefs, Access to Healthcare, Financial Constraints, Stigma, Fear, and delayed referral. Many parents may not be aware of the importance of early diagnosis and treatment of undescended testis. Some families may hold cultural beliefs that discourage medical intervention or prioritize traditional remedies over surgical options.4 In some regions, access to healthcare facilities may be limited, and families may face challenges in reaching specialized care. The cost of treatment can be a barrier for many families, leading to delays in seeking appropriate care. There may be stigma associated with conditions affecting male reproductive health, causing parents to delay seeking treatment out of fear of embarrassment.5 In conclusion, patients with undescended testes are still being brought late for surgical correction. Even decades after proved that: delay in UDT treatment correlates with many health issues, such as torsion, infertility and malignant changes. We are still having late presentation with undescended testes. This problem can be overcome by thorough examination of newborns, increasing parents’ awareness regarding UDT and by updating the knowledge of health care provider regarding prompt UDT management.